INCREASING PRODUCTIVITY OF SCLUPTOR IN KAPAL VILLAGE, BADUNG, BALI - Ni Kadek Pujiani Dewi (Journal of Industrial Engineering and Halal Industries, 2020)
To increase the productivity, modern hand tools such as electrical grinder, electrical drill and band saw have been used by the scluptor in Kapal village. Due to ignorance, in using them not all precaution were taken into consideration. Also squatting and bending positions produced many complaints. Therefore, an ergonomics intervention has been conducted. Using multistage random sampling technique, 20 subjects were sampled from the scluptors. Blood pressure, and heart rate were measured, and subjective feelings were recorded using Nordic Body Map, before and after working for a week. The results showed that after working; 1.2% increased in systolic blood pressure; 4.7% increased HR per minute; and 20.7% subjective complaints (p<0.05). To overcome the problems ergonomics intervention have been conducted which consist of three types as follows: 1) advising to have rest pause 3-5 minutes in every one hour working; 2) the workplace for electrical grinder must be separated from another workplaces, and the operator of electrical grinder machine should have a rest after 30 minutes, in case the electrical grinder could not be separated all workers there should use cotton car plugs. 3) the physical fitness of scluptors should be improved by doing exercise program 3-5 times per week. After two weeks of awareness program, responses found as follows: 87% of workers engaged in having short rest pauses 90% of workers engaged in using ear plugs and 77% were engaged fitness program. The preliminary results showed there are a decreased in systolic blood pressure 0.46%, (p>0.05). HR 4.96% (p<0.05), subjective complaints 18.39% (p<0.05), and associated by an increased of productivity at about 17.55% (p<0.05).